Neuronal and Axonal Loss in Normal-Appearing Gray Matter and Subpial Lesions in Multiple Sclerosis. Issue 5 (May 2015) - Klaver, Roel; Popescu, Veronica; Voorn, Pieter; Galis-de Graaf, Yvonne; van der Valk, Paul; de Vries, Helga E.; Schenk, Geert J.; Geurts, Jeroen J.G.
<x xml:space="preserve">Abstract</x> Abstract Multiple sclerosis (MS) is a demyelinating and neurodegenerative disease of the CNS. Multiple sclerosis lesions include significant demyelination of the gray matter, which is thought to be a major contributor to both physical and cognitive impairment. Subpial (Type III) lesions are the most common demyelinated cortical lesions. We investigated neurodegenerative features of subpial lesions in cerebral cortex samples from 11 patients with MS and 6 nondemented non-MS controls. There were no significant differences in neuron and axon density between normally myelinated normal-appearing gray matter (NAGM) and Type III MS lesions. Neurons were 11.2% smaller in Type III lesions than in NAGM in the cingulate cortex only; Type III lesions contained 25.4% fewer NeuN-positive neurons compared with control cortex. Neurons in MS NAGM were 13.6% smaller than those in control cortex. Finally, the same regions, immunostained with anti-SMI312 antibodies, showed reduced axon densities in Type III lesions (−31.4%) and NAGM (−33.0%) compared with controls. In conclusion, both NAGM and Type III lesions showed neurodegenerative changes, but they had no consistent differences in neuronal and axonal alterations. This suggests that neurodegeneration in the cerebral cortex of patients with MS may be independent of cortical demyelination.